Lightning-induced effects in electrical and telecommunication systems - Baba, Yoshihiro; Rakov, Vladimir A., 1955- (IET energy engineering series ;, 2020)
Providing an overview of modelling and understanding lightning-related effects on complex power and telecommunications systems, this book explores both traditional transmission-line theory as well as the state-of-the art finite difference time-domain (FDTD) method.